Comprehensive management of rotator cuff tendinopathy in diabetic patients with Ayurveda and myofascial release - P. M., Shifana; Ravoof P. K., Abdul; T. C., Marikutty; M. S., Aneesh (International Journal of Research in Medical Sciences, 2025)
Shoulder disorders are markedly more common in individuals with diabetes than in the general population. Rotator cuff tendinopathy, a form of persistent tendon pain and dysfunction from mechanical loading, arises when tendon regeneration fails, leading to structural disorganization, thickening, and potential rupture. Its etiology involves intrinsic factors such as aging, altered tendon biology, vascular compromise, and overload, as well as extrinsic factors including impingement from structural variations, soft-tissue tightness, muscle imbalance, and overuse, all of which contribute to compromised tendon integrity and function. A 49-year-old male patient who is a known case of Diabetes mellitus was admitted to Kayachikitsa IPD of Vaidyaratnam Ayurveda College, Ollur on 09 July 2024 with bilateral shoulder joint pain more at right side with stiffness and limited range of motion. He underwent a treatment protocol of vatavyadhi and myofascial release with an effort to keep diabetes under control. The patient got relief from pain (VAS score 6 to 1) and stiffness and range of movements were improved. There is remarkable functional restoration (SPADI 57.69 to 10). In rotator cuff tendinopathy of diabetic patients, a combined use of pramehahara oushadha, vatavyadhi chikitsa and myofascial release can be effective.